Checklist of the Heleomyzidae, Neriidae and Oestridae (Insecta, Diptera) in the State of Mato Grosso do Sul, Brazil (2012)
ABSTRACT: We provide a checklist of fl ies of the families Heleomyzidae, Neriidae, and Oestridae in the State of Mato Grosso do Sul, Brazil. Heleomyzidae are represented in Brazil by 13 species, and only Neorhinotora aristalis (Fischer) is recorded to the State of Mato Grosso do Sul. The two reported species of Neriidae, Longina abdominalis Wiedemann and Nerius pilifer Fabricius, are among the 15 species now known in Brazil. The Oestridae family is represented by two species distributed in two genera: Dermatobia hominis (Linnaeus Jr.) and Cuterebra rufi ventris Macquart.